Blue Tongue Virus in Dairy Cattle of Minas Gerais, Brazil - Serological Survey - Neves dos Reis, Jairo; Varaschin, Mary Suzan; Dorneles, Elaine Maria Seles; Barbieri, Jonata de Melo; Diniz Matos, Ana Carolina; Lobato, Zélia Inês Portela; Ribeiro, Paula Reis; da Silva, Ana Beatriz de Souza; Raymundo, Djeison Lutier (Acta Scientiae Veterinariae, 2022)
Background: Blue tongue (BT) is a noncontagious viral disease transmitted by hematophagous arthropods, especially of the genus Culicoides. The economic impact of the disease is related not only to deaths in sheep herds but also to the possible correlation of virus infection with the development of other diseases, such as pneumonia, abortion and movement problems. The economic losses caused by Blue Tongue are linked to restrictions on the import and export of animals and their genetic material and to the reproductive disorders associated with this disease. In addition, the fact that cattle take the role of reservoir, combined with the care by other countries with outbreaks of infection and biological contamination of their products, hinders trade in Mercosul, United States and Europe. Cattle are affected by Blue Tongue Virus in endemic areas and in some epidemic areas, but the development of clinical disease is rare. The clinical signs, when evident, range from reproductive losses, such as embryonic death, abortion, fetal malformation, temporary sterility, infertility in bulls, stillbirths and the birth of weak animals. The objective of this study was to determine the epidemiological aspects of Blue Tongue Virus (BTV) infection in dairy cattle in the Lavras region, state of Minas Gerais, Brazil. Materials, Methods & Results: A cross-sectional study was conducted to evaluate the frequency of cattle and herds seropositive for Blue Tongue in the southern region of Minas Gerais. In this study, 54 dairy farms were visited. A total of 586 serum samples were collected from female cattle of reproductive age. Sampling was random, and serum samples were collected from lactating cows over 24 months of age by puncture of the jugular vein and/or coccidian vein. The samples were transported and stored at the Setor de Patologia Veterinária, at the Universidade Federal de Lavras (SPV-UFLA), where they were centrifuged, and the serum aliquots were obtained, transferred to microtubes and kept at -20 °C until the serological tests were performed. The samples were tested with the agarose gel immunodiffusion test (AGID) for anti-blue tongue virus antibodies. The AGID test is more practical and is the main method used to identify Blue Tongue Virus seroprevalence in different ruminant species. They are considered important tools for epidemiological surveillance of the disease. A prevalence of 83.28% was observed among animals that were seropositive for Blue Tongue Virus (488/586; IC 95% = 80.0 - 86.21). In addition, 100% (54/54; IC 95% = 93.4 - 100.0) of the farms had at least one positive animal, with rates ranging from 45.45% to 100% within the herds and where 22.22% of the farms had rates of 100% of the animals being positive. Discussion: Blue Tongue is a disease known to affect domestic and wild ruminants in Brazil. However, there is a lack of more precise information about its epidemiology and occurrence in the country and of joint efforts of researchers, producers and the government to understand in detail both the biology of vectors and the viral biology of Blue Tongue Virus in Brazil. This is the first record of detection of anti-blue tongue virus antibodies in cattle in the southern region of Minas Gerais. The results suggest that Blue Tongue Virus is present in cattle in the study area. Keywords: BTV, prevalence, AGID, anti-BTV antibodies, Orbivirus, Reoviridae.